2018
DOI: 10.22159/ijap.2018.v10s1.19
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Study of Association Between Glycemic Control and Quality of Life Among Diabetic Patients

Abstract: Objective: The present study aimed to evaluate the association between glycemic control and quality of life (QoL) in people with type 2 diabetes mellitus (T2DM) and identify that factors that influence glycemic control and QoL. Methods:This cross-sectional study was conducted at the general hospital in Depok City from October to December 2017. Respondents were outpatients diagnosed with T2DM, receiving routine care at the hospital. Glycemic control was assessed using glycated hemoglobin (HbA1c) levels, while Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
5
2
Order By: Relevance
“…18 In two studies that were conducted in Indonesia, the mean health utility of patients with type 2 diabetes was 0.74 and 0.77, respectively. 19,20 Compared to these previous findings, the results of the present study, determined there was a health utility value of 0.294 ± 0.371, which is quite low. Moreover, this low health utility value was found to improve in conjunction with the healing.…”
Section: Discussioncontrasting
confidence: 95%
“…18 In two studies that were conducted in Indonesia, the mean health utility of patients with type 2 diabetes was 0.74 and 0.77, respectively. 19,20 Compared to these previous findings, the results of the present study, determined there was a health utility value of 0.294 ± 0.371, which is quite low. Moreover, this low health utility value was found to improve in conjunction with the healing.…”
Section: Discussioncontrasting
confidence: 95%
“…For patients with diabetes mellitus (Table 2), 12 studies reported health utility values ranging from 0.31 to 0.99 (14,15,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). The Chinese standard EQ-5D-5L value set (18) and Crosswalk UK value set (24) were used to derive the utility values in the studies that reported the highest value and lowest value, respectively.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…The results showed that the utility value calculated with the Uruguay value set was the highest at 0.880, while the lowest, 0.735, was derived with the value set from the Netherlands. The EQ-5D VAS scores were reported to range from 50.9 to 72.6 in six studies (14,20,(22)(23)(24)(25). Among the five dimensions of the EQ-5D-5L, pain/discomfort was the dimension with the most reported problems.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…2) with molecular formula C 4 H 11 N 5 .HCl. The main mechanism of metformin HCl was lowering glucose intestinal absorption, inhibition of hepatic glucose production, and improving glucose uptake and utilization [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%